Progresifitas Hukum dalam menguatkan nilai-nilai Pancasila - Amrina Rosyada Rina (Faculty of Sharia and Law UNISNU Jepara, 2021)
Along with the development of civilization and the demands of the times, all will experience challenges to be able to lead to the goal and the peak of benefit. Just like the Law will also experience development along with the times and civilization. This development can be described in terms of progress. More familiar is the progressive law; Satjipto Rahardjo. How the law is able to provide answers to problems and solutions to the problems of life. Laws that have been running in Indonesia must be strengthened in an effort to achieve justice and humanity. As has been mandated in Pancasila, which is the basis of the state. The law is advanced and harmonized with the values of Pancasila is an effort to realize a just law, in the sense of the word commensurate with the violation committed. The progress of the law in responding to problems that cannot be separated from the values of Pancasila is expected to contribute to efforts to improve the law in the State of Indonesia. The law which is the basis of the Indonesian state must be pursued as much as possible so that it becomes a country that truly upholds what it believes in and is made the basis of the state. Seiring berkembangnya Peradaban dan juga tuntutan zaman semua akan mengalami tantangan untuk mampu mengarahkan kepada Tujuan dan puncak kemanfaatan. Sama seperti halnya Hukum juga akan mengalami perkembangan dengan seiringan zaman dan peradaban. Perkembagan ini bisa dibahasakan dengan istilah kemajuan. Yang lebih familiar adalah hukum Proresif; Satjipto Rahardjo. Bagaiamana hukum mampu memberikan jawaban atas permasalahan dan solusi dari problematika kehidupan. Hukum yang sudah berjalan di indonesia harus di kuatkan dalam upaya mencapai keadilan dan kemanusiaan. Seperti yang sudah di amanahkan didalam Pancasila, yang menjadi dasar negara. Hukum maju dan diselaraskan dengan nilai-nilai Pancasila adalah usaha untuk mewujudkan hukum yang adil, dalam arti kata sepadan sesuai dengan pelanggaran yang di lakukan. Progresifitas hukum dalam menjawab permasalahan yang tidak lepas dari nilai-nilai Pancasila diharapkan memberikan kontribusi dalam upaya perbaikan hukum di Negara Indonesia. Hukum yang menadi dasar negara indonesia harus diupayakan semaksimal mungkin agar menjadi negara yang memang memegang teguh apa yang di yakini dan di jadikan dasar negara.